ASSESSMENT OF CRITICAL BARRIERS TO TENDER PRICE INDICES DEVELOPMENT IN THE GHANAIAN BUILDING INDUSTRY - Ernest KISSI; Theophilus ADJEI-KUMI; Peter AMOAH; Emmanuel BOATENG BANNOR (Journal of Construction Project Management and Innovation)
The development of the tender price indices (TPI) in developed countries expands to over some decades in terms of its application. In contrast, these indices are not available in developing countries owing to the fact that their development is constrained by some perceived critical barriers. Thus, the aim of the study was to identify the critical barriers to the development of tender price indices. Using the quantitative research method, data were collected from quantity surveyors and then analysed using the mean score and principal component analysis (PCA). The findings highlighted five (5) underlying critical barriers, namely poor procurement and estimating, erratic external and project conditions, data unavailability, technological implications, and weak knowledge base. The findings suggest that there is an urgent need for practitioners to build their capacity in order to facilitate the development of TPI. It is further recommended that these barriers should be addressed meticulously as it serves as the basis for the advancement of knowledge of the tender price index in Ghana and other developing countries.